Research and Optimization of High-voltage IGBT Module Short CircuitCharacteristics for Traction Application - LIU Guo-you; QIN Rong-zhen; HUANG Jian-wei; Ian Deviny; WU Yi-bo; YU-Wei (机车电传动)
Three IGBT short circuit types had been introduced. The short circuit type 2 had been enhanced through optimization of theIGBT transistor gain to withstand higher short circuit current. Additionally, the IGBT short circuit over current had been suppressed by thegate drive clamping design. As a result, the high-voltage IGBT modules had successfully passed the short circuit testes required by tractionapplication.